A Case of An Unusual Foreign Body in the Esophagus - A. L. Charyshkin; I. I. Gumerov; M. V. Yashkov; L. V. Matveyeva (Неотложная медицинская помощь, 2019)
Abstract Relevance. Esophageal foreign body may be safely removed with rigid esophagoscopy. However, endoscopic methods are not always successful, and this may require a surgery. Aim of study We report a case of an unusual esophageal foreign body.Materials and methods A 34-year-old male patient P. with a foreign body in the esophagus. Endoscopic, radiological, and laboratory diagnostic methods were performed to confirm a foreign body in the esophagus.Results A rare clinical observation of a 34-year-old male patient P. with a foreign body in the esophagus is presented (package with psychoactive substances). After an unsuccessful attempt to remove a foreign body using esophagoscopy, thoracotomy was performed and a foreign body was mechanically brought down into the stomach without opening the lumen of the esophagus. In the postoperative period, the condition was serious, the patient had been in coma for 10 days. There was hectic fever on day 7. On day 9, the left thoracotomy was performed, the revision showed no damage to the esophagus. Urine analysis for psychoactive substances was performed and detected tetrahydrocannabinol acid and aminochlorobenzophenone, a derivative of 1,4-benzodiazepine. On day 9, after repeated surgery, the patient confirmed the fact of swallowing a package of psychoactive substances, being conscious. On day 14 after the second operation, the patient was transferred to the regional narcological hospital.Conclusion In patients with a foreign body in the esophagus in difficult clinical situations, it is necessary to collect anamnesis carefully, apply endoscopic, radiological and laboratory diagnostic methods, including urinalysis for psychoactive substances.